Analisis Pemanfaatan Sistem APG X Atas Sistem Pembayaran Jasa Tenaga Kerja Bongkar Muat Pupuk Pada PT. Pupuk Sriwidjaja Palembang - Ulfa, Sapuro; Khairani, Siti (Universitas Bandar Lampung (UBL), 2025)
This research is a qualitative research that aims to find out how the payment system for fertilizer loading and unloading labor (TKBM) services after the use of the APG X system and the impact of the APG X system on the payment system for fertilizer TKBM services at PT Pupuk Sriwidjaja Palembang. Data collection techniques through observation and interviews. The results showed that at the beginning of the implementation process of APG X system utilization at PT. Pusri Palembang there are technical and social challenges where social challenges there are still differences in vendor perceptions in using the APG X system, especially vendors in the East Java region and new vendors and technical challenges need to be developed on the APG X system to make it easier for vendors to use the APG X system without further data processing, besides that the utilization of the APG X system has a positive impact on the payment of fertilizer TKBM services to vendors of PT Pusri Palembang where vendors are faster in billing because of the ease of completing billing documents, preventing the potential for double billing by vendors and a good impact on the vendor's cash flow because it is faster to receive payment for fertilizer TKBM services.